2012
DOI: 10.1177/030006051204000619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Transareola Singlesite Endoscopic Thyroidectomy and Minimally Invasive Video-assisted Thyroidectomy

Abstract: Patients treated with TASSET had superior cosmetic results compared with those treated with MIVAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…These results are in accordance with previous studies. 11,12 In conclusion, transareola single-site endoscopic thyroidectomy is safe and feasible and has the advantages of a covert incision, minor subcutaneous separation area, and high cosmetic satisfaction. With the increased number of patients undergoing such surgery, the duration of operation will be shortened.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results are in accordance with previous studies. 11,12 In conclusion, transareola single-site endoscopic thyroidectomy is safe and feasible and has the advantages of a covert incision, minor subcutaneous separation area, and high cosmetic satisfaction. With the increased number of patients undergoing such surgery, the duration of operation will be shortened.…”
Section: Discussionmentioning
confidence: 91%
“…10 Because of the presence of these disputes, transareola single-site endoscopic thyroidectomy was designed in 2012 and has been demonstrated to be associated with improved cosmetic results and minimal invasiveness. 11,12 In this study, we report a further 28 cases who underwent transareola single-site endoscopic thyroidectomy in Fengxian Central Hospital (Shanghai, China) from January 2010 to April 2012. Good therapeutic outcomes were achieved, and no one was converted to an open approach.…”
Section: Introductionmentioning
confidence: 99%
“…7, 8 We successfully performed transareola single-site endoscopic unilateral thyroidectomy in patients and established promising modality. 9 With an increase in experience, we gradually expanded surgical indications and performed transareola single-site endoscopic bilateral thyroidectomy in selected cases. Transareola single-site endoscopic thyroidectomy is performed in a unidirectional view and a single channel.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported advantages of transareola single-site endoscopic thyroidectomy for a unilateral thyroid nodule compared with open thyroidectomy or minimally invasive video-assisted thyroidectomy, including better cosmetic results, a lower rate of postoperative complications, and better completion rate for surgery. [7][8][9] However, transareola single-site endoscopic bilateral thyroidectomy remains a technically challenging procedure. Because dissection of the bilateral thyroid nodules needs to cross the trachea, the two-dimensional visual representation and use of nonflexible endoscopic instruments can make it difficult to visualize the surgical field adequately and to manipulate instruments.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of oncological radicality and safety, as proposed by the evidence‐based practices of enhanced recovery after surgery, 14 real minimal invasion also plays a critical part in enhanced recovery 15 . Trans‐areolar single‐site endoscopic thyroidectomy (TASSET) only leaves a tiny unilateral incision and minimizes the subcutaneous dissection area 11,13 . Nevertheless, due to technical challenges, this practice is rarely attempted, and only a limited number of cases have been reported 16 .…”
Section: Introductionmentioning
confidence: 99%